PENGARUH TRANSFER PRICING, KEPEMILIKAN ASING, KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Fitriani, Dwi Nur; Djaddang, Syahril; Suyanto, Suyanto (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
This study attempts to examine the association between transfer pricing, foreign ownership, institutional ownership, corporate social responsibility, and tax aggressiveness of multinational manufacturing companies that listed on Indonesia Stock Exchange for the years 2016 to 2019. Beside that this study attempts to analyze the simultaneous and partial association between transfer pricing, foreign ownership, institutional ownership on tax aggressiveness with corporate social responsibility as a moderate variable. The analytical method that used in this study are statistic descriptive and moderated regression analysis (MRA) by using SPSS version 25. The sample selection technique used was purposive sampling and obtained 12 multinational manufacturing companies for the years 2016 to 2019 that results in 48 samples. The results of this study indicate that transfer pricing and institutional ownership have an effect on tax aggressiveness. Meanwhile, foreign ownership has no effect on tax aggressiveness. The results of the research moderated by corporate social responsibility get the results that it can weaken the influence of transfer pricing and institutional ownership on tax aggressiveness. Meanwhile, foreign ownership with corporate social responsibility as moderation has no effect on tax aggressiveness.